2022
DOI: 10.1177/20420188221099337
|View full text |Cite
|
Sign up to set email alerts
|

Association of continuous glucose monitoring-derived time in range with major amputation risk in diabetic foot osteomyelitis patients undergoing amputation

Abstract: Objective: The metrics generated from continuous glucose monitoring (CGM), such as time in range (TIR), are strongly correlated with diabetes complications. This study explored the association of perioperative CGM-derived metrics with major amputation risk in patients with diabetic foot osteomyelitis (DFO). Methods: This study recruited 55 DFO patients with grade 3–4 wounds according to the Wagner Diabetic Foot Ulcer Classification System, all of whom underwent CGM for 5 days during the perioperative period. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…42 The 10 observational studies focused on glycaemic surrogates, and five reported significant reductions in the frequency of hypoand hyper-glycaemia events, as well as less glucose variability. 20,21,30,31,34 One observational study also included the assessments of health outcomes and reported that hypoand hyper-glycaemia profiles were negatively associated with diabetes complications after controlling for potential confounders. 31 3.3.2 | CGM benefits in combination with other treatments and devices 13 reports aimed to describe CGM benefits in combination with other devices or treatments.…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…42 The 10 observational studies focused on glycaemic surrogates, and five reported significant reductions in the frequency of hypoand hyper-glycaemia events, as well as less glucose variability. 20,21,30,31,34 One observational study also included the assessments of health outcomes and reported that hypoand hyper-glycaemia profiles were negatively associated with diabetes complications after controlling for potential confounders. 31 3.3.2 | CGM benefits in combination with other treatments and devices 13 reports aimed to describe CGM benefits in combination with other devices or treatments.…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 99%
“…The pre‐post study focusing on T2DM showed a reduction in HbA 1c levels after 3 months 42 . The 10 observational studies focused on glycaemic surrogates, and five reported significant reductions in the frequency of hypo‐ and hyper‐glycaemia events, as well as less glucose variability 20,21,30,31,34 . One observational study also included the assessments of health outcomes and reported that hypo‐ and hyper‐glycaemia profiles were negatively associated with diabetes complications after controlling for potential confounders 31 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have explored the relationship between the TIR and biochemical parameters of blood glucose such as HbA1c, glycated albumin, and 1,5-anhydro-d-glucitol [25][26][27][28][29] as well as metrics derived from CGM such as the GMI, ambulatory glucose profile indexes, and the CV. 26,[30][31][32] Concurrently, a steadily increasing amount of evidence emerged indicating that the TIR can predict the risk of chronic complications of diabetes such as diabetic retinopathy, 33 diabetic polyneuropathy, 34,35 diabetic foot amputation, 36,37 macrovascular disease, 38 and even cancer mortality. 39 We further divided our patients into those with a TIR of ≤70% (non-target group) and those with a TIR of >70% (target group) according to the 70%TIR boundary mentioned above.…”
Section: Discussionmentioning
confidence: 99%